Peningkatan Kapasitas Kader Posyandu Lansia melalui Pelatihan Penerapan 5 Meja di Desa Ngestirejo, Tanjungsari Gunungkidul - Margaretha Kurniastuti; Bernadetta Eka Noviati; Emmelia Ratnawati (Universitas Negeri Gorontalo, 2025)
Ngestirejo Village has a high proportion of elderly residents (30% or approximately 1,800 people) but limited cadres and low participation, making cadre training essential to enhance the capacity of elderly health services for more optimal and integrated implementation. This community service activity aims to form and train kader in managing elderly posyandu using the 5-table system. The activity was conducted using a training method with the topic “Elderly Posyandu with the 5-Table System,” followed by a simulation of the elderly posyandu. Evaluation of the activity was carried out using a pretest and posttest. A total of 25 participants attended the training. Posttest evaluation results showed that the knowledge level of the kader regarding the implementation of the Elderly Posyandu with the 5-Table System improved significantly. The majority (94%) or 23 participants experienced an increase in knowledge, while only a small portion (8%) or 2 participants showed no improvement. The GIN improvement results showed that 40% of participants experienced an increase of 15 points. The simulation of the elderly posyandu demonstrated enthusiasm from both the kader and elderly representatives in participating in the 5-table posyandu activity, indicating a positive increase in knowledge and engagement.